A Comparison of Cholesterol Uptake and Storage in Inflammatory and Noninflammatory Breast Cancer Cells. (31st December 2012) - Martin, Breonna J.; van Golen, Kenneth L.
Abstract : Although there are many subtypes of breast cancer, inflammatory breast cancer (IBC) is arguably the deadliest. Research over the past decade has demonstrated that IBC is a distinct entity from other forms of breast cancer. Important risk factors that have been associated with the development of aggressive breast cancers, such as IBC, include obesity and diet, which are evident in the United States, where the overconsumption of high-fat foods continues to contribute to obesity in the nation. Here we investigate differences in cholesterol uptake and storage between IBC, non-IBC, and mammary epithelial cell lines. Our results demonstrate that compared with human mammary epithelial cells (HMECs), both IBC and non-IBC cells have increased cholesterol content. IBC cells retain intracellular cholesterol esters, free cholesterol, and triglycerides in lipid-deficient environments. In contrast, we observe in cell-type-of-origin-matched non-IBC a significant decrease in lipid content under the same lipid-deficient conditions. These data suggest that cholesterol storage may be affected by the cholesterol content of the environment where the tumor cell was isolated. Here, we suggest that breast cancer cells may migrate when they are unable to obtain cholesterol from their extracellular environments.